Mapping and Conservation of Cold-Water Corals in the Lacaze-Duthiers Canyon for Transboundary Management - FABRI, MARIE-CLAIRE; DREIDEMY, JEANNE; ESTOURNEL, CLAUDE; VAZ, SANDRINE; MICHEZ, NOËMIE; PUIG, PERE; LARTAUD, FRANCK (Mediterranean Marine Science, 2025)
Cold-water coral habitats (Madrepora oculata and Desmophyllum pertusum) were mapped in the Lacaze-Duthiers Canyon, within the “Parc naturel marin du golfe du Lion” (northwestern Mediterranean), to support the creation of a strongly protected area for these vulnerable marine ecosystems (VME). The analyses are based on ROV data, high-resolution digital terrain models (5–10 m), hydrodynamic model simulations (currents, temperature, salinity from SYMPHONIE), and fishing pressure data derived from Vessel Monitoring System (VMS) and Automatic Identification System (AIS) fishing data. Habitat models indicate coral habitats are mainly on the western canyon flank (250 to 600 m depth). Desmophyllum pertusum predominantly colonizes gentle slopes at cliff bases, while M. oculata is found on steeper slopes, and the eastern flank. Some western flank areas support both species. Direct impacts from fishing activities, including lost longlines and nets entangled with corals, were observed. In addition, bottom trawling at the continental shelf edge induces sediment resuspension, potentially smothering the underlying coral ecosystems in the canyon. This study recommends enhancing fishing activity monitoring by increasing VMS positioning transmission frequency across European countries and facilitating the combination of VMS and AIS data to derive higher-resolution fishing effort and footprint assessments. Protection should prioritize canyon flanks and the surrounding continental shelf, not just the canyon itself, to mitigate fishing pressure. Tailored management measures are needed for sensitive habitats. Creating a strongly protected area will require crossborder cooperation (France, Spain) to ensure the effective conservation of these fragile ecosystems.